More than words an exploratory study on the use of generational slang in Philippine online news outlets using a media linguistics approach - Jimenez, Ronin Xavier A.; Manaois, Mervin John K.
This thesis determines how major Philippine online media sites use generational terms and slang in their articles. Journalists produce texts that the public reads. The language, slang, and terminology reporters employ mirrors the broader society and its culture, which may make their work more relevant and engage the audience when reading. To explore how online news outlets in the Philippines use generational terms and slang, the researchers inspected historical and cultural contexts, identified and analyzed generational terms and slang in articles from Rappler.com, Inquirer.net, and Philstar.com throughout their earliest (1999) to latest (2025) publications via corpus analysis and various software applications for data gathering and organization. Textual data gathering involved six parameters: authorship, type of production and presentation, media channel, genre, and topical affiliation. Results showed that Philippine online news flexibly used generational terms and slang words according to the years they were popular. Future studies are recommended to explore the underlying themes of each news publication’s sections and sociocultural implications that may impact how journalists adapt their writing style to fit current trends, especially in a digital setting.